ANTI-FERROPORTIN MONOCLONAL ANTIBODIES AND USES THEREOF - LEUNG, Donmienne, Doen, Mun; TANG, Ying; LUAN, Peng; WITCHER, Derrick, Ryan; MANETTA, Joseph, Vincent (2012)
Provided are monoclonal antibodies and antigen-binding fragments thereof that bind to, and inhibit the activity of human FPN1, and which are effective in maintaining or increasing the transport of iron out of mammalian cells and/or maintaining or increasing the level of serum iron, reticulocyte count, red blood cell count, hemoglobin, and/or hematocrit in a subject in vivo.